Necessity of preschool library in preschool education institutions for the reading habits culture in Turkey [Türkiye'de okuma alişkanliği kültürü için okul öncesi eğitim kurumlarinda anaokulu kütüphanelerinin gerekliliği] - (:unkn) unknown (T.C. Milli Egitim Bakanligi, 2015)
When the history of our culture of reading and library use habits, no term has this habit it seems to be the basis of Turkish society. Both state and nongovernmental organizations in policy, children will have a say in the future of the country, an approach that embraced the book and library culture, demonstrates that continued lack of infrastructure in this regard. Because of the habit of reading in the family culture is also extremely poor, but the settlement of a book and library concept of pre-school children's minds in pre-school educational institutions seems to be possible with the establishment of the "Preschool Libraries". The aim of this study is to make the reading habit and culture in Turkey, to provide pre-school children in mind the formation of books and libraries perception and to emphasize the need for it preshool library.
Keywords: Culture of reading habits; Preschool; Preschool libray; Reading habits